ELECTROENCEPHALOGRAM AND VISUAL EVOKED POTENTIAL CHANGES Study IN PATIENTS PRESENTED WITH PRIMARY HEADACHES - Mohammed, Nidaa S.; Abbas, Farah N.; Albermani, Abud AlK.; AbudAlameer, Wahab. R. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
A headache is pain anywhere in the region of the head or neck. The most common types of primaryheadaches are migraines and tension-type headaches. They have different characteristics. Migrainestypically present with pulsing head pain, nausea, photophobia (sensitivity to light) and phonophobia(sensitivity to sound). Tension-type headaches usually present with non-pulsing "band like" pressure onboth sides of the head, not accompanied by other symptoms. Other very rare types of primary headacheswhich included, Cluster headaches, Trigeminal autonomic cephalgia and Chronic daily headaches.